Design and Construction of Cu(OH)2/Ni3S2 Composite Electrode on Cu Foam by Two-Step Electrodeposition - Sa Lv; Wenshi Shang; Huan Wang; Xuefeng Chu; Yaodan Chi; Chao Wang; Jia Yang; Peiyu Geng; Xiaotian Yang (Micromachines, 2022)
A Cu(OH)2/Ni3S2 composite has been designed and in situ constructed on Cu foam substrate by facile two-step electrodeposition. Cu(OH)2 is achieved on Cu foam by galvanostatic electrodeposition, and the subsequent coating of Ni3S2 is realized by cyclic voltammetric (CV) electrodeposition. The introduction of Cu(OH)2 provides skeleton support and a large specific surface area for the Ni3S2 electrodeposition. Benefiting from the selection of different components and preparation technology, the Cu(OH)2/Ni3S2 composite exhibits enhanced electrochemical properties with a high specific capacitance of 4.85 F cm−2 at 2 mA cm−2 and long-term cyclic stability at 80.84% (4000 cycles).